Gender differences in self-reported sleep problems among older adults in six middle-income countries: a cross-sectional study. (3rd September 2022) - Rani, Ritu; Arokiasamy, Perianayagam; Selvamani, Y.; Sikarwar, Ankit
ABSTRACT: This study examines gender differences in sleep problems among older adults in India, China, Ghana, Mexico, Russia, and South Africa. We used data on 33, 929 individuals (50+ years) from the WHO-SAGE. Results showed significant gender differences in the prevalence of sleep problems with the largest difference in Russia followed by India. Regression results showed higher odds of sleep problems among women in India, China, Russia, and South Africa. Age, low back pain, depression, and poor self-rated health were significantly associated with sleep problems. This research confirms significant gender differences in sleep problems among the older population in middle-income countries.